New species of the genus Phaonia R.-D., 1830 (Diptera, Muscidae) from Central Asia - Sorokina, Vera S. (Zootaxa, 2015)
A list of species of Phaonia Robineau-Desvoidy, 1830 of Central Asia is given, and four new species of Phaonia are described from Tajikistan, Uzbekistan and Turkmenistan (P. babarabica sp. nov., P. juglans sp. nov., P. modesta sp. nov. and P. ninae sp. nov.). The male terminalia of all species and ovipositors of P. ninae sp. nov. and P. modesta sp. nov. are figured. Previous literature on the genus Phaonia in Central Asia is reviewed.